Cardiotoxicity of HER2-targeted therapies - Copeland-Halperin, Robert S. (Curr Opin Cardiol, 2019)
PURPOSE OF REVIEW: Cardiotoxicity is a well recognized adverse effect of human epidermal growth factor receptor 2 (HER2)-targeted therapies. The goal of this review is to highlight recent studies that have advanced our knowledge of the diagnosis, prevention, and management of cardiotoxicity associated with HER2-targeted agents. RECENT FINDINGS: Several clinical risk factors for cardiotoxicity associated with HER2-targeted therapies have been identified including age, low-baseline left ventricular ejection fraction, and treatment with anthracyclines; however, these remain insufficient to identify all patients at risk for cardiotoxicity. Routine cardiac monitoring remains the standard for cardiotoxicity surveillance, although the optimal frequency and modality of monitoring remains uncertain. Global longitudinal strain, T1/T2 weighted CMR imaging protocols, and circulating biomarkers can detect early signs of cardiotoxicity, but studies are needed to investigate whether use of these markers in clinical practice improves patient outcomes. Cardioprotective medications (e.g. beta-blockers or ACE-inhibitors) may be of benefit to patients at increased risk for cardiotoxicity from HER2-taregeted therapies, particularly those who are treated with an anthracycline-containing regimen. SUMMARY: Improved risk stratification of patients during HER2-targeted therapy and effective prevention and management strategies for cardiotoxicity are needed to enhance the value of longitudinal cardiac monitoring and increase cardiac safety so that optimal breast cancer treatment can be delivered.